An isogeometric formulation for stability analysis of laminated plates and shallow shells. (October 2019) - Praciano, Jamires Sousa Cordeiro; Barros, Pedro Sanderson Bastos; Barroso, Elias Saraiva; Parente, Evandro; Holanda, Áurea Silva de; Sousa, João Batista M.
Abstract: Laminated composite plates and shells have been widely used in aeronautical, mechanical, and naval structures. Stability is a major concern in the design of these structures due to their high slenderness. Therefore, it is necessary to properly analyze their post-critical behavior, assessing their sensitivity to initial imperfections and load-carrying capacity. This paper presents a methodology based on the Isogeometric Analysis to study the stability of laminated plates and shallow shells. In this formulation, the geometry and displacement field are described using NURBS basis functions. Appropriate integration schemes are used to avoid the locking problem for thin-walled plates and shells. The proposed formulation was applied in the stability analysis of various examples and excellent results were obtained. The influence of the composite layup and geometric imperfections on the buckling load and post-critical behavior is studied. New bifurcation solutions to a well-known laminated shell buckling benchmark problem are presented. Highlights: A NURBS-based isogeometric formulation for nonlinear analysis of laminated shallow shells is presented. The formulation can be applied to the stability analysis of perfect and imperfect laminated plates. Appropriate integration schemes are used to avoid shear locking problem for thin-walled plates and shells. Excellent results were obtained for plates and shells with different layups. New solutions to a well-known shell buckling benchmark problem are presented.